2013
DOI: 10.2146/ajhp120267
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a pharmacist-managed heart failure medication titration clinic

Abstract: Implementation of a pharmacist-managed HF medication titration clinic increased the percentage of patients achieving optimal ACEI, ARB, and β-blocker dosages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 21 publications
1
62
0
Order By: Relevance
“…47 Studies have also evaluated pharmacist-managed medication titration in HF. 37,38 Recognising the key role that general practitioners (GPs) play in HF management, Lowrie et al undertook a cluster-RCT of nonspecialist, pharmacist-managed medication titration in 1,090 HFrEF patients attending 87 practices in United Kingdom. While this study did not achieve its primary clinical endpoint, a higher proportion of patients who enrolled in practices with pharmacist-assisted titration achieved target doses of ACEI therapy.…”
Section: Medication Titration Intervention Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…47 Studies have also evaluated pharmacist-managed medication titration in HF. 37,38 Recognising the key role that general practitioners (GPs) play in HF management, Lowrie et al undertook a cluster-RCT of nonspecialist, pharmacist-managed medication titration in 1,090 HFrEF patients attending 87 practices in United Kingdom. While this study did not achieve its primary clinical endpoint, a higher proportion of patients who enrolled in practices with pharmacist-assisted titration achieved target doses of ACEI therapy.…”
Section: Medication Titration Intervention Studiesmentioning
confidence: 99%
“…38 In a before-after, retrospective design study targeting 51 higher-risk HFrEF patients conducted in the United States, Martinez et al demonstrated that a multifaceted intervention, which included pharmacist-managed titration guided by telephone monitoring, resulted in a higher proportion of patients achieving target doses of ACEI/ARB and beta-blockers. 37 We recently undertook a quality improvement study that aimed to embed a pre-designed medication titration plan into standard clinical practice for patients newly referred to the HF services in three hospitals. 48 This study involved completing and faxing a customised medication titration form to the patient's GP on the day of hospital discharge that clearly defined which healthcare provider was primarily responsible for medication titration.…”
Section: Medication Titration Intervention Studiesmentioning
confidence: 99%
“…(9) Heart failure disease management (HFDM) programs improve outcomes in patients recently discharged from hospital, helping to provide a "bridge" between hospital and primary care. (14) Specialized HF medical clinics or protocol-driven nurse and pharmacist led clinics can be effective in improving titration following hospitalization (15)(16)(17)(18) although this finding has not been universal. (6) HFDM services may help to address barriers by providing access to specialized multidisciplinary staff familiar with current guidelines, who have the time and skills to support medication monitoring.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…23 Although these trials in hypertension were in the setting of the prevention of heart disease as opposed to the therapy for HF, the principles of organized or protocol-driven patient review with stepped pharmacotherapy using the assistance of nurses and pharmacists has a direct application to the titration of HF pharmacotherapy. Pharmacist-led titration has been shown to increase the percentage of patients receiving optimal HF drug dosing, 24 and nurse-led phone-based intervention may increase both the proportion of patients achieving the trial-defined optimal dose and may improve left ventricular ejection fraction and reduce the need for device therapy in HF. 25 Diabetes Diabetes is present in more than one-third of Medicare recipients with HF.…”
Section: Hypertensionmentioning
confidence: 99%